Comparative analysis of sperm count, hormonal profile and testicular volume before and after intra-testicular PRP therapy in non-obstructive azoospermia - Banu, Jesmine; Sultana, Rebeka; Alamgir, Chowdhury Faisal; Darmini, Maliha; Mahmud, Khan Shihan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Non-obstructive azoospermia (NOA) is a major cause of male infertility, with limited treatment options. Platelet-rich plasma (PRP), which is rich in growth factors, has been proposed as a regenerative therapy. This study conducted a comparative analysis of sperm count, hormonal profiles and testicular volume before and after intratesticular autologous PRP therapy in men with NOA. Methods: This self-controlled clinical trial was conducted at the Department of Reproductive Endocrinology and Infertility, BSMMU, Dhaka, from January 2022 to July 2023. Thirty men with NOA underwent intratesticular injection of autologous PRP (2–3 ml per testis). Baseline and follow-up assessments at 1 and 3 months included semen analysis, clinical and ultrasound measurements of serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone and testicular volume. Data were analyzed using SPSS v26. Results: No spermatozoa were detected in semen samples at baseline, 1 month or 3 months post-treatment. Hormonal profiles showed mild fluctuations without significance (FSH: 33.1 to 24.3 mIU/ml, p=0.061, LH: 9.5 to 9.6 mIU/ml, p=0.562, testosterone: 392.0 to 435.1 ng/dl, p=0.062). Mean testicular volume increased from 9.5±2.3 ml to 11.2±2.4 ml (p=0.004) using the Prader orchidometer and from 10.0±2.4 ml to 11.3±2.4 ml (p=0.002) using ultrasound. Side effects included transient pain (20.0%) and hematoma (20.0%), with no infections reported. Conclusions: Intratesticular PRP increased testicular volume but did not restore spermatogenesis or alter hormones significantly in NOA patients. Although safe and biologically plausible, its clinical utility requires validation through larger, long-term trials.